Characterization of Rongchang piglets after infection with type 2 porcine reproductive and respiratory syndrome virus strains differing in pathogenicity - Zhang, Wenli; Ma, Wenjie; Pan, Yu; Wang, Xinrong; Wang, Mengjie; Zhang, He; Gao, Junxin; Zhang, Hongliang; Tian, Zhijun; Li, Changwen; Chen, Hongyan; Xia, Changyou; et al. (Frontiers in Microbiology, 2023)
Porcine reproductive and respiratory syndrome virus (PRRSV) affects the production and health of pigs and causes severe economic losses to the swine industry worldwide.Different pig breeds have been reported to have different levels of susceptibility to PRRSV, and different PRRSV strains may also influence the infectivity and pathogenicity of the virus. In this study, the susceptibility of Rongchang pigs (a prominent local pig breed in China) to PRRSV infection was thoroughly investigated. Rongchang piglets were exposed to two PRRSV strains: HuN4 (highly pathogenic PRRSV) and SD53-1603 (moderately virulent NADC30-like PRRSV). We observed that Rongchang pigs infected with HuN4 displayed significant clinical manifestations, including fever, reduced body weight, and interstitial pneumonia lesions. Routine blood tests revealed that HuN4-infected pigs exhibited slightly decreased levels of red blood cells, hemoglobin, reticulocytes, and a notable increase in monocytes than control pigs. Additionally, the Rongchang pigs exhibiting severe clinical signs presented a higher neutrophil-to-lymphocyte ratio and a lower lymphocyte-to-monocyte ratio. In contrast, SD53-1603 infection did not cause considerable harm to Rongchang pigs, only resulting in slightly elevated leukocytes and lymphocytes. Furthermore, these two PRRSV strains elicited divergent cytokine responses, such that SD53-1603 infection induced higher levels of TNF-α and IFN-γ, whereas HuN4 infection upregulated IL-1β. These dissimilarities in clinical symptoms, pathological changes, viremia, cytokine expression, and routine blood indices between HuN4 and SD53-1603 infections are critical in understanding the mechanisms of PRRSV infection and developing rational prevention and control strategies against PRRSV.